OzoNews Volume XIX - 30 July 2019 - United Nations Environment Programme (2019)
In this issue: 1. Update on new refrigerants designations and safety classifications - factsheet 2. Why do Antarctic Ozone recovery trends vary? 3. Architecture and financing models for efficient cooling alongside the Montreal Protocol - Discussion paper 4. The role of refrigeration in the global economy 5. Montreal Protocol and Legal Experts from Southern African Development Community countries team up for Kigali Amendment 6. Training-workshop on refrigeration and air conditioning - Eritrea 7. Philippines on right track in global phaseout of HCFC 8. Protect your business: Buy refrigerants from safe sources! 9. Introduction to refrigeration standard EN 378 10. Revised Part 2 of the Guide to Good Commercial Refrigeration Practice series